Analysis of User Satisfaction of PELNI Website with WebQual 4.0 and TAM Methods - Syam, Arniati; Dedi I. Inan; Ratna Juita; Merlinda Sanglise; Lorna Y. Baisa (STMIK Budi Darma, 2024)
The success of an organization is heavily influenced by the quality of its website in the current digital era. PT Pelayaran Nasional Indonesia (PELNI), as one of the State-Owned Enterprises (BUMN) that plays a crucial role in sea transportation in Indonesia, understands the importance of having an effective website to support its mission and vision. Therefore, PT Pelayaran Nasional Indonesia (PELNI) has developed a website that aims to facilitate the public in accessing information and services related to sea transportation. The analysis of user satisfaction with the PT Pelayaran Nasional Indonesia (PELNI) website is the particular goal of this study. The methods used in this research are WebQual 4.0 and the Technology Acceptance Model (TAM). A total of 103 respondents using the PELNI website participated in this study, where data was collected through a Google Form-based questionnaire. The analysis's findings indicate that a number of factors, including usability, perceived usefulness, information quality, system quality, and informativeness, positively and significantly affect user satisfaction (T-Statistic> 1.96 at the 5% significance level and P-Value <0.05). However, variables such as Perceived Ease of Use and Service Quality do not show a significant effect on user satisfaction (T-Statistic < 1.96 and P-Value > 0.05). These findings can serve as a foundation for PELNI to make further improvements and development to their website, with the aim of improving service quality and better meeting user needs